Pengaruh Model Pembelajaran Berbasis Masalah terhadap Keterampilan Pemecahan Masalah Peserta Didik Kelas VIII SMPN 2 Mattiro Bulu - Marwah Marwah; Ramlawati Ramlawati; Sitti Saenab (Celebes Science Education, 2023)
This research aims to: (1) knowing the level of problem solving skills of students after using problem based learning model in class VIII SMPN 2 Mattiro Bulu, (2) knowing the level of problem solving skills of students after using conventional learning model in class VIII SMPN 2 Mattiro Bulu and, (3) knowing the problem solving skills of students who are using the Problem Based Learning model are higher than the problem solving skills of students who are using the Direct Learning model in class VIII of SMPN 2 Mattiro Bulu. The population is class VIII SMPN 2 Mattiro Bulu consisted of 5 classes with 80 students. Taking technique of sample is random sampling. The research sample consist of two classes, namely class VIII.1 as a experiment class with 15 students and class VIII.5 as a control class with 15 students. The data were gathered by testing the students’ problem solving skill which were analyzed by using t-test. Results of descriptive statistical analysis of problem solving skills of students using problem based learning model be the high category, while the direct learning model is in the category of medium. Results of inferential statistical analysis were ttable=2,86 ttable=2,04. Based on the results of the research Problem Based Learning (PBL) model be in the high compared the conventional learning model in the category of medium which means the problem based learning model affects to IPA Problem Solving Skill on Students ClassVIII SMPN 2 Mattiro Bulu on the subject matter of vibrations waves and sounds.